PCR-based random amplified polymorphic DNA fingerprinting of Yersinia pseudotuberculosis and its practical applications. - Makino, S (1994)
The random amplified polymorphic DNA (RAPD) fingerprinting method was used to distinguish between various strains of Yersinia pseudotuberculosis, a causative agent of gastroenteritis in humans. The RAPD test uses arbitrarily chosen DNA oligomers of 10 nucleotides to prime DNA synthesis from genomic sites to which they are accidentally matched or almost matched. Most 10-nucleotide primers yielded strain-specific arrays. Ten Y. pseudotuberculosis type strains were distinguishable from each other by analyzing the RAPD arrays produced by using primers with a 50% G+C content. The RAPD patterns of Y. pseudotuberculosis strains were found to be constant regardless of the presence or absence of the large plasmid. RAPD tests were subsequently used to identify 30 clinical isolates of Y. pseudotuberculosis that were collected as the causative agent of an outbreak of Izumi fever, a disease showing clinical symptoms characteristic of atypical scarlet fever, in Japan. The RAPD arrays from all of the isolates yielded common patterns that were unique to each primer used. Since those 30 isolates belonged to serotype 5a and the restriction digest patterns of their large plasmids were all the same, the results of the RAPD tests confirmed the view that those isolates were from a single source and indicated that the RAPD test can be practically applied to survey transmission of the bacterium in humans.